Transition of a deep eutectic solution to aqueous solution: a dynamical perspective of the dissolved solute - Sakpal, Sushil S.; Deshmukh, Samadhan H.; Chatterjee, Srijan; Ghosh, Deborin; Bagchi, Sayan (Journal of Physical Chemistry Letters, 2021)
Disruption of the deep eutectic solvent (DES) nanostructure around the dissolved solute upon addition of water is investigated by polarization-selective two-dimensional infrared spectroscopy and molecular dynamics simulations. The heterogeneous DES nanostructure around the solute is partially retained up to 41 wt % of added water, although water molecules are gradually incorporated in the solute's solvation shell even at lower hydration levels. Beyond 41 wt %, the solute is observed to be preferentially solvated by water. This composition denotes the upper hydration limit of the deep eutectic solvent above which the solute senses an aqueous solvation environment. Interestingly, our results indicate that the transition from a deep eutectic solvation environment to an aqueous one around the dissolved solute can happen at a hydration level lower than that reported for the ``water in DES'' to ``DES in water'' transition.